2000
DOI: 10.1177/0011128700046004007
|View full text |Cite
|
Sign up to set email alerts
|

Sanction Threats in Court-Ordered Programs: Examining Their Effects on Offenders Mandated into Drug Treatment

Abstract: During the past decade, court-ordered diversion and treatment procedures have proliferated in response to the problems of court congestion and prison overcrowding. Underlying these court orders are stiff sanctions that are often used to threaten offenders to comply with the court's mandate. Given the widespread use of court orders and their stiff penalties for violations, the effectiveness of sanction threats in enforcing compliance among offenders has rarely been examined. Using a sample of offenders mandated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 17 publications
0
42
3
Order By: Relevance
“…Furthermore, this finding contradicts the often-reported belief that legal compulsion improves treatment retention [6,20] , which is based mainly on empirical studies that fail to use adequate comparison groups or employ rather short follow-up periods [6,8] . However, we could not confirm perceived family pressure as a relevant, negative predictor in a study on 3 US therapeutic communities [24] .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, this finding contradicts the often-reported belief that legal compulsion improves treatment retention [6,20] , which is based mainly on empirical studies that fail to use adequate comparison groups or employ rather short follow-up periods [6,8] . However, we could not confirm perceived family pressure as a relevant, negative predictor in a study on 3 US therapeutic communities [24] .…”
Section: Discussioncontrasting
confidence: 61%
“…Previous research combining different measures of coercion has produced some interesting results. For example, an American study in 3 inpatient therapeutic communities found that perceived legal pressure predicts better retention, while pressure from families predicts worse retention [24] . Stevens et al [25] suggested that participants entering QCT perceive more pressure, but this does not necessarily lead to higher or lower motivation than under voluntary treatment.…”
Section: Perceived Pressure and Coercionmentioning
confidence: 99%
“…For example, an American study in three residential therapeutic communities found that perceived legal pressure did predict better retention, but legal status had mixed effects, while pressure from families predicted worse retention [21] . Wild et al [19] reported that, in their study of 300 people entering drug treatment, 35% of those who were legally mandated reported that they perceived no pressure, while 37% of non-mandated clients reported that they felt some coercion.…”
Section: Previous Researchmentioning
confidence: 99%
“…The need to independently assess objective and subjective aspects of coercion has been identified in other studies as well. For example, Maxwell [45] similarly reported that actual legal status and self-reported legal pressure exhibited independent effects on treatment retention. The ethnographic study of Wolf and Colyer [46] identified subtypes of participants exposed to the same drug court procedures.…”
Section: What Is the Relationship Between Compulsory Treatment And Comentioning
confidence: 99%